PENGARUH KEUANGAN ISLAM TERHADAP PERTUMBUHAN EKONOMI NEGARA BERPENDUDUK MAYORITAS ISLAM DI ASEAN - Saputra, Dika; Putri, Dewi Zaini (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study aims to look at the influence of Islamic finance on the economic growth of Muslim-majority countries in ASEAN. The data used is panel data over the 2004-2018 times period in the three Islamic Majority Country in ASEAN. The variable used are economic growth (Y), Islamic Financial Depth (X2), Islamic banking asset (X2), and Islamic Banking Activiti (X3). This research method uses panel data analysis. This study found that the Islamic Financial Depth variable had a signficant effect on economic growth, the variable Islamic banking asset and Islamic banking activities had a signficant effect on economics growth with alpha 0.05. Overall there is a signficant influence of Islamics financial variables on economic growth in Muslim-majority countries in ASEAN. Therefore, the government must support activity related to Islamic finance especially in Islamic banking so that the performance of Islamics banking can maximize and contribute to economic activity and encourage economic growth.